ANALISIS FAKTOR KUALITAS JASA TERHADAP KEPUASAN PELANGGAN DI WAROENG CETAKAN CIMAHI - Dzulfa Amalia Putri Pratiwi; Sa’ad Noor (Politeknik Negeri Lhokseumawe, 2022)
Abstract: Waroeng Cetakan is a company engaged in the printing sector, To maintain and improve customer satisfaction, The company always strives to provide products with better service quality, The purpose of this study was to determine the factors of service quality on customer satisfaction, This study uses the service quality variable (X) as an independent variable consisting of tangible, reability, responsiveness, asurance , emphati and customer satisfaction variables (Y) as dependent variable. The surveys were distributed to 99 respondents using a non-probability sampling technique Then, using SPSS V25, statistical tests (validity, correlation coefficient, coefficient of determination, and hypothesis testing) were performed. The results of data analysis are obtained tarithmetic ttable (7.663 1.988). The value is adjusted R square 0.484 or 48.4% for variables emphati and the significance value of all accumulated service quality (X) 0.000 0.005 which means Service quality has a significant positive effect on customer satisfaction based on the SPSS report. ThisKeywords: Quality, Service, Customer satisfaction